Increased labor market participation can't do the job of mastering Germany's demographic change in the future - Karl Brenke; Marius Clemens (DIW Economic Bulletin, 2017)
In the last decade the available labor force has expanded in Germany-despite the decline in the working-age population. The reason: labor market participation has increased, for women in particular and older people in general. Also noticeable was a rise in qualification level because well-educated people have a particularly high propensity to participate in the labor market. Most recently, Germany's potential labor force has grown as a consequence of many factors, including migration-from other EU member states in particular. The immigrants from EU countries now exhibits higher labor market participation than that of Germans. This is due to the favorable age structure of the migrants from the EU. The situation is different overall for migrants from non-member states: their participation is relatively low. This may have to do with lack of access to the job market. However, another factor is that the participation of women from non-member states is far below the average. In the future, Germany will be more or less reliant on migration. This is the finding of various model calculations showing the effects of demographic influences and participation behavior on Germany's future labor supply. Even if Germany's level of labor market participation rises to Switzerland's current level by 2040, the finding still applies. The Swiss example shows that policy makers were successful at attracting persons with higher labor market participation from abroad. In Switzerland, the labor market participation of older people is also much higher than in Germany. Policy makers in Germany should take that into account and ensure that skill potential is not prematurely lost to early retirement. Granting tax and social contribution privileges to the semiretired is counterproductive.
Keywords: E24; J11; J21; 330; labor force; labor market participation; demographic shift; migration